Revisiting the relationship between stomatal size and speed across species – a meta‐analysis - Woning, Nik; Al‐Salman, Yazen; Kaiser, Elias; Berman, Sarah R.; Brendel, Oliver; Cano, Francisco Javier; Carpentier, Sebastien; Centritto, Mauro; Drake, Paul L.; Durand, Maxime; Eyland, David; Franks, Peter J.; et al. (Wiley, 2025)
The rate of stomatal opening and closure in response to changes in light affects leaf photosynthesis and water use. However, it is unclear how strongly stomatal size ( SS ) and density ( SD ) influence stomatal conductance ( g s ) kinetics, and whether variation arises from methodological differences, guard cell type or degree of amphistomaty. We divided published records combining stomatal kinetics and anatomical traits from 89 species into kidney and dumbbell‐shaped guard cells, and evaluated four dynamic g s models on them. We derived the time constant for an exponential response of g s ( τ ) and the maximum rate of change ( Sl max ) as well as the ratio of adaxial/abaxial SD ( rSD ). We found significant differences in parameter estimation between models. Stomatal anatomical traits and kinetic parameters showed large variation across species. While individual anatomical features ( SS , SD , rSD and guard cell types) were weakly correlated with stomatal response speed ( τ and Sl max ), interactions between these features showed significant effects, demonstrating that kinetic performance arises from synergistic rather than additive anatomical relationships. Our results call for the use of our unified modeling approach, challenge the generality of the observation that smaller stomata move faster across species and suggest rSD as an understudied driver of stomatal kinetics.